Gastroesophageal Reflux Disease and Bronchial Asthma: Updated View on the Problem of Comorbidity - Hanych T. (Львівський клінічний вісник)
Introduction. Recently, much attention is paid to comorbidity. It is proved that in patients with bronchial asthma (BA) gastroesophageal reflux occurs significantly more frequently than in general population (70.0–80.0 %), which naturally provokes interest to this consolidation. As early as 1892, W. Osler first described an attack of an aspiration caused by aspiration of gastric contents, initiating the study of reflux induced asthma. Scientists distinguish a number of factors that influence its occurrence: the weakness of the esophageal sphincter, the failure of induced cardia, the keel of the esophagus, the reduction of the resistance of the mucous membrane of the esophagus due to the constant irritation of the reflux, discoordination of the swallow reflex and the closure of the vocal cavity, and also the occurrence of reflux in the bronchial tree. Aim. To describe the contemporary views on the problem of comorbidity of gastroesophagal reflux disease (GERD) and BA. Materials and methods. Content analysis, method of system and comparative analysis, bibliosemantic method of the study of actual scientific research concerning the problem of comorbidity of GERD and BA was used. Results. Lung function testing results analysis performed in our study, showed that patients with both BA and reflux had significantly lower values of volume parameters, whereas velocity parameters did not significantly differ from those without reflux, suggesting more pronounced restrictive lung abnormalities in asthmatic patient with gastroesophageal reflux diseases (GERD). Besides, subjects with asthma and GERD combination were less responsive to bronchodilator therapy and therefore had worse asthma control. Despite the fact that BA combined with GERD has more severe course and poorer response to treatment, the results of study regarding efficacy of anti-reflux therapy were ambiguous. Although after such therapy the majority of patients with erosive form of GERD demonstrated both less severe asthma symptoms and lower demand in controller medications, there was no any improvement in the results of lung function testing. In patients with asymptomatic GERD the treatment had no effect on the clinical presentations and asthma control. Conclusions. There is a need for further study of causation and treatment strategy in patients with a combination of BA and gastroesophageal reflux. After all, timely diagnosis and treatment of erosive forms of GERD in such patients make it possible not only to avoid complications, but also to reduce the manifestations of asthma.